COMPARE OF THE ISLAMIC BANKING SYSTEM AT INDONESIA AND MALAYSIA - Yunda, Lola Irma; Rangkuty, Dewi Mahrani; Saputra, Jumadil; Rusiadi, Rusiadi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Indonesia and Malaysia play a pivotal role in propelling the advancement of Islamic banking and finance in Southeast Asia. The progress of Islamic banking and finance systems in these two nations serves as a catalyst, encouraging other countries in the region to engage in the development of the Islamic banking and finance industry. This study aims to explore and compare the Islamic banking systems in Indonesia and Malaysia. The research employs a descriptive qualitative approach through a literature review. The institutional frameworks of Islamic banking in Indonesia and Malaysia exhibit numerous similarities, particularly concerning the central bank. The central banks in both countries hold the highest authority in overseeing, guiding, and formulating policies for financial institutions, especially within the Islamic banking sector.